WOMEN’S PERCEPTION OF THE ACTUALISATION OF THE 5TH MDG (REDUCTION OF MATERNAL MORTALITY): A STUDY OF PREGNANT WOMEN IN IMO STATE, NIGERIA - Fab-Ukozor, Nkem; Ejem, Agwu A. (European Scientific Journal, ESJ, 2015)
Goal number five of the Millennium Development Goals (MDG), reduction of maternal mortality, had always represented a major challenge for Nigerian women. As the deadline for the actualization of the goals approaches, this study examined Nigerian women’s perception of the attainment of the target goal. Pregnant women registered in health facilities in Imo State, Nigeria, were purposively studied. For this study, 210 pregnant women were sampled in 21 (5%) out of the 416 documented health facilities in the State. Using data gathered over a sampling period of 11 days by means of questionnaire and oral interview, analyses were done using a combination of qualitative and quantitative methods. The analyses found out that Nigeria was making progress in reducing maternal mortality rates, but the pace still remains too slow, as there are still many instances of deaths related to childbirth. Factors responsible for the slow progress were given as low ratio of births attended by skilled health workers, especially in rural areas; unfortunate attitudes to antenatal and postnatal care, poor state of health/medical infrastructure, etc. This study recommended the need for Nigeria to declare primary health care as a national emergency in 2015 and implement policies that will bring about structural change in the health sector and behavioural change among pregnant women.